Alterations of Interhemispheric Functional Connectivity in Parkinson’s Disease With Depression: A Resting-State Functional MRI Study - Liao, Haiyan; Fan, Jie; Shen, Qin; Cai, Sainan; Wang, Min; Wang, Chunyu; Zhang, Hainan; Liu, Jun; Zhu, Xiongzhao; Tan, Changlian (Frontiers in Human Neuroscience, 2020)
Background: Depression is the most common non-motor symptom in patients with Parkinson’s disease (PD) with unknown mechanisms, while the diagnostic criteria of PD with depression are not uniform. Purpose: To investigate interhemispheric interactions between PD patients with and without depression. Methods: The voxel mirrored homotopic connectivity (VMHC) combined with the seed-based method was used to investigate intrinsic resting-state functional connectivity (RSFC) in 33 PD patients with depression (PDD), 60 PD patients without depression (PDND), and 47 healthy controls (HCs). Results: PDD patients exhibited a decreased VMHC in the bilateral medial frontal gyrus and paracentral lobule (MFG/PCL) when compared to PDND. PDD had a decreased VMHC in the bilateral precentral gyrus (PCG) when compared to PDND and HC (p < 0.05). PDD had a decreased homotopic RSFC from the middle frontal gyrus (MFG)/ paracentral lobule (PCL) to the contralateral supplementary motor area (SMA) when compared to PDND (p < 0.05). The decreased homotopic RSFC from the right MFG/PCL to the left SMA was negatively correlated with Hamilton Depression Rating Scale (HDRS) scores (p < 0.05), but not with illness duration, BDI, and UPDRS-III in PD patients. Conclusions: Our findings indicated that the occurrence of depression in Parkinson’s disease is associated with the dysfunctional connectivity from the MFG/PCL to the contralateral SMA, which could be used as potential neuroimaging markers for the diagnosis of depression in PD patients.